Mechanisms of activation of nucleus accumbens neurons by cocaine via sigma-1 receptor–inositol 1, 4, 5-trisphosphate–transient receptor potential canonical channel pathways. Issue 2 (1st August 2015) - Barr, Jeffrey L.; Deliu, Elena; Brailoiu, G. Cristina; Zhao, Pingwei; Yan, Guang; Abood, Mary E.; Unterwald, Ellen M.; Brailoiu, Eugen
Graphical abstract